Descripbing of the Evaluation Process in Balai Besar Pendidikan dan Pelatihan Kesejahteraan Sosial (BBPPKS) Regional I Sumatra - Redha Syofian; Irmawita Irmawita (Universitas Negeri Padang, 2019)
This research is motivated by the way the implementation of learning education and training goes well, each year the participants' learning outcomes increase. So this study suggests looking at an overview of the evaluation process in Balai Besar Pendidikan dan Pelatihan Kesejahteraan Sosial (BBPPKS) Regional I Sumatra in Padang City which contains evaluations of inputs, processes, outputs, results, and influences. This type of research is quantitative descriptive research, with a population of 30 people. The sample in this study replaced 20 participants, who were determined using cluster random sampling techniques. The technique of delivering data in this study uses a questionnaire, while the data analysis technique used in this study is percentage. Based on the results of this research, research that found evaluation of input and influence was in good category, and process evaluation, updates, and results in a pretty good category.Keywords: Process Evaluation, Education and Training, BBPPKS